Human Brain Phantom Modeling Based on Relative Permittivity Dielectric Properties - Chew, Kim Mey; Rubita, Sudirman; Norhudah, Seman; Yong, Ching Yee (2012)
This study aims to investigate the clinical outcomes of human brain dielectric properties in order to build a human-like brain phantom using simple material. This artificial intelligence human brain was developed according to the dielectric properties of a real human brain. The regions cover grey matter and white matter tissues. Elements used for phantom building demonstrate adequate internal consistency of er (relative permittivity) within 60-80 for a range of frequency from 1-6 GHz. A surprisingly finding, quantity of element sugar is the main reason of affecting the permittivity. The findings give a big step closer for building an artificial human brain without defect.